Schooling Relates to Mental Health Problems in Adolescents with Cochlear Implants—Mediation by Hearing and Family Variables - Huber, Maria; Pletzer, Belinda; Giourgas, Alexandros; Nickisch, Andreas; Kunze, Silke; Illg, Angelika (Frontiers in Psychology, 2015)
Aim of this multicenter study was to investigate whether schooling relates to mental health problems of adolescents with cochlear implants (CI) and how this relationship is mediated by hearing and family variables. 140 secondary school students with CI (mean age = 14.7 years, SD = 1.5), their hearing parents and teachers completed the Strengths and Difficulties Questionnaire (SDQ). Additional audiological tests (speech comprehension tests in quiet and noise) were performed. Students of special schools for hearing impaired persons (SSHIs) showed significantly more conduct problems (p<0.05) and a significantly higher total difficulty score (p<0.05) compared to students of mainstream schools. Mental health problems did not differ between SSHI students with sign language education and SSHI students with oral education. Late implanted students and those with indication for additional handicaps were equally distributed among mainstream schools and SSHIs. However, students in SSHIs were more restricted to understand speech in noise, had a lower social background and were more likely to come from single-parent families. These factors were found to be partial mediators of the differences in mental health problems between the two school types. However, no variable could explain comprehensively, why students of SSHIs have more mental health problems than mainstream pupils.